Monitoraggio strumentale eGIS: Applicazioni e soluzioni per il monitoraggio delle infrastrutture e le grandi opere - Parboni, Stefano; Morino, Alberto; Valdermarin, Federico (GEOmedia, 2014)
Monitoraggio strumentale eGIS: Applicazioni e soluzioni per il monitoraggio delle infrastrutture e le grandi opere